Pelaksanaan Pekerjaan Pengawasan Pada Proyek Pembangunan Drainase Ruas Jalan Ciseuti-Bunihayu Kecamatan Jalancagak - Jajang Nurjaman; Deny Ernawan (MESA (Teknik Mesin, Teknik Elektro, Teknik Sipil, Teknik Arsitektur), 2022)
Independent Internship Independent campus learning is part of the independent campus program which aims to provide opportunities for students to learn and develop themselves through activities outside of the lecture class. During the internship, students apply direct learning in the workplace with hard skills which can be started from skills in the field of work, problem solving, and analysis of problems in the world of work, as well as soft skills such as ethics in the world of work, organization and management, as well as collaboration between teams in the world Work. The conclusion of the Merdeka Learning internship at the Merdeka Campus is that students are able to improve their soft skills and hard skills and gain new experiences that can later be applied in the world of work. The author did an MBKM internship at the Subang Regency PUPR Service and was placed in a supervisory position in the bridge sector. Based on the results of observations in the field, the stages of implementation of the drainage project development are quite in accordance with the theoretical standards for implementing drainage development, it's just that it may not be too complex due to adjustments to conditions in the field.